LKB1 destabilizes microtubules in myoblasts and contributes to myoblast differentiation. - Isma Mian; Willythssa Stéphie Pierre-Louis; Neha Dole; Renée M Gilberti; Kimberly Dodge-Kafka; Jennifer S Tirnauer (PLoS ONE)
Background Skeletal muscle myoblast differentiation and fusion into multinucleate myotubes is associated with dramatic cytoskeletal changes. We find that microtubules in differentiated myotubes are highly stabilized, but premature microtubule stabilization blocks differentiation. Factors responsible for microtubule destabilization in myoblasts have not been identified. Findings We find that a transient decrease in microtubule stabilization early during myoblast differentiation precedes the ultimate microtubule stabilization seen in differentiated myotubes. We report a role for the serine-threonine kinase LKB1 in both microtubule destabilization and myoblast differentiation. LKB1 overexpression reduced microtubule elongation in a Nocodazole washout assay, and LKB1 RNAi increased it, showing LKB1 destabilizes microtubule assembly in myoblasts. LKB1 levels and activity increased during myoblast differentiation, along with activation of the known LKB1 substrates AMP-activated protein kinase (AMPK) and microtubule affinity regulating kinases (MARKs). LKB1 overexpression accelerated differentiation, whereas RNAi impaired it. Conclusions Reduced microtubule stability precedes myoblast differentiation and the associated ultimate microtubule stabilization seen in myotubes. LKB1 plays a positive role in microtubule destabilization in myoblasts and in myoblast differentiation. This work suggests a model by which LKB1-induced microtubule destabilization facilitates the cytoskeletal changes required for differentiation. Transient destabilization of microtubules might be a useful strategy for enhancing and/or synchronizing myoblast differentiation.